PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TIPE TANDUR DITINJAU DARI MOTIVASI BELAJAR SISWA - Ade Miftah Fauzi; Kurnia Noviartati (Jurnal Pembelajaran Matematika, 2018)
Abstract: Conventional learning can be considered as one factor that causes low learning motivation of students in Junior High School (SMP). Learning with a pleasant atmosphere can stimulate students’ motivation and encourage them to construct knowledge. Quantum teaching is offered as a solution to engage with the problem. The objective of this study is to determine the effect of quantum teaching learning of TANDUR type viewed from students’ learning motivation. This is pre-experimental research with one-group pretest-posttest design. The instrument is motivational questionnaire. The subjects of this study are all students at VII A of Private Junior High School (SMP) in Surabaya as an experimental class. The results show that there is a significant difference on students’ learning motivation who follow TANDUR type of quantum teaching learning model. It is proved by the results of pretest and posttest data analysis using t test. The value of  is 5.09 then it is compared to value of , namely 2.05 with significant level of  and . Based on this, it can be concluded that quantum teaching learning model of TANDUR type has a positive influence on students’ learning motivation because .Keywords: Learning Motivation, Quantum Teaching Learning.